Reestablishing Legal Certainty in Dispute Resolution for Digital Transactions Based on Influencer Marketing in Indonesia - Hilda Pebriani; Muhamad Abdul Ghofur Subekhi; Bunga Metha; Naufal Farhan; Regina Nur Fuadzah; Muhamad Reja Zaelani; Hilmansyah Hilmansyah; Nandang Najmudin (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the reconstruction of legal certainty in dispute resolution for digital transactions based on influencer marketing in Indonesia through a normative juridical approach. The research employs statutory and conceptual analyses to evaluate the adequacy, coherence, and normative consistency of legal instruments governing relationships among businesses, influencers, consumers, and digital platforms. Primary legal materials include the Indonesian Civil Code, Consumer Protection Law, Electronic Information and Transactions Law and its amendment, and Government Regulation concerning Electronic Systems and Transactions. The findings reveal that existing legal arrangements have not provided a sufficiently integrated framework for determining liability, resolving disputes, and ensuring accountability within influencer driven commercial activities. Normative ambiguity emerges from the complex interaction among contractual obligations, consumer protection principles, electronic transaction regulations, and platform governance responsibilities. The study further demonstrates that legal certainty depends on a clear allocation of rights and obligations among transactional actors supported by effective institutional mechanisms. A reconstruction model is proposed through regulatory harmonization, integrated online dispute resolution, strengthened consumer protection, explicit influencer liability provisions, and shared platform accountability. The proposed framework aims to improve dispute resolution effectiveness, enhance market trust, and support sustainable governance of Indonesia’s digital economy.